Induction and inhibition of the allantoin permease in Saccharomyces cerevisiae. - Sumrada, R (1978)
Allantoin uptake in Saccharomyces cerevisiae is mediated by an energy-dependent, low-Km, active transport system. However, there is at present little information concerning its regulation. In view of this, we investigated the control of alloantoin transport and found that it was regulated quite differently from the other pathway components. Preincubation of appropriate mutant cultures with purified allantoate (commercial preparations contain 17% allantoin), urea, or oxalurate did not significantly increase allantoin uptake. Preincubation with allantoin, however, resulted in a 10- to 15-fold increase in the rate of allantoin accumulation. Two allantoin analogs were also found to elicit dramatic increases in allantoin uptake. Hydantoin and hydantoin acetic acid were able to induce allantoin transport to 63 and 95% of the levels observed with allantoin. Neither of these compounds was able to serve as a sole nitrogen source for S. cerevisiae, and they may be non-metabolizable inducers of the allantoin permease. The rna1 gene product appeared to be required for allantoin permease induction, suggesting that control was exerted at the level of gene expression. In addition, we have shown that allantoin uptake is not unidirectional; efflux merely occurs at a very low rate. Allantoin uptake is also transinhibited by addition of certain amino acids to the culture medium, and several models concerning the operation of such inhibition were discussed.